Halal Labels and Buyer Decisions: Roland Barthes’ Semiotics - Sumarna, Imam Budi; Milki Rijal Ashari; Suci Putri Lestari (Universitas Pasundan, 2026)
The influence of halal labels on consumer purchasing decisions from the semiotic perspective of Roland Barthes. Halal labels, which are often found on food and beverage products, have a significant role in shaping consumer perceptions, especially among Muslim consumers. Through Barthes' semiotic approach, the halal label is understood as a sign consisting of two elements: signifier and signified. The signifier is a physical label displaying halal certification, while the signified includes the meaning of halal, hygiene, quality, and religious identity. This analysis is conducted by distinguishing two levels of meaning: denotative and connotative. Denotatively, the halal label indicates that the product meets halal standards. However, at the connotative level, the label relates to broader values, such as trust, safety, health, and compliance with Islamic law. The results show that the connotative meaning of the halal label has a strong influence on the purchasing decisions of Muslim consumers, who often see this label as a representation of Islamic identity and lifestyle. The halal label not only serves as a product information tool, but also plays an important role in shaping purchasing preferences and decisions through cultural and religious meanings.